The Occult Roots of MTV: British Music Video and Underground Film-Making in the 1980s. Issue 1 (July 2017) - Fowler, William
Abstract : This article provides a new exploration of the British underground film scene and its influence on, and relationship with, pop video tropes and techniques, and MTV. It considers the rich sub-cultural interrelations of the early 1980s that embraced esoteric ideas, queer occultism, punk, postmodernism, British art schools, Derek Jarman, William S. Burroughs, home video, Scratch Video, Video Nasties, Super 8, Michael Jackson, Grayson Perry, John Maybury, the Avebury Ring, Duran Duran, Maurice Merleau-Ponty, Dr John Dee, Jean Cocteau, and Neneh Cherry. The article establishes the unique film and television context and culture in the UK at the turn of the 1980s which enabled experimental and underground film-making practices to reach a wider audience through innovative programming opportunities at Channel 4 and via the expanding medium of music video. It describes the powerful, exploratory nature of independent filmmaking that existed at this time and its basis in British art schools; several of the practitioners subsequently went on to major careers as pop video directors, demonstrating a two-tiered influence on both the industry, and moving image aesthetics over the next twenty years. This article was published open access under a CC BY licensehttps://creativecommons.org/licenses/by/4.0/